(untitled) (Faridpur Medical College Journal, 2011)
Bronchial asthma is an atopic disease characterized by chronic airway inflammation and hyper-responsiveness. Severe acute asthma is a medical emergency and sometimes difficult to treat. This prospective study was done at Dhaka Medical College Hospital from January 1997 to January 1998. Total 30 patients of bronchial asthma were included in this study. Diagnosis was established on the basis of symptoms, evidence of airflow obstruction and its reversibility by bronchodilator therapy. The age range was 18 to 80 years with a mean 36.64±4.91. Of them, 63% were male and 37% were female. It revealed that all patients had classical triad of dyspnoea, wheeze and cough. Almost all patients (80%) had some precipitating agents for their attack. Regarding treatment of severe acute asthma - Nebulized salbutamol is superior to conventional intravenous aminophylline, as p value of nebulized salbutamol group is <0.001 which is significant. So, severe acute asthma should be managed with nebulized salbutamol instead of intravenous aminophylline. Key words: Bronchial asthma; Bronchodilator; Nebulized salbutamol; Aminophylline. DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9211 FMCJ 2011; 6(2): 100-103